Improved functional oral intake and exercise training attenuate decline in aerobic capacity following chemoradiotherapy in patients with esophageal cancer - Shu-Chun Huang; Lan-Yan Yang; Yin-Kai Chao; Wei-Yang Chang; Ya-Tzu Tsao; Chuan-Yi Chou; Ching-Chung Hsiao; Chien-Hung Chiu (Medical Journals Sweden, 2024)
Purpose: To investigate the impact of chemoradiotherapy on the physical fitness of patients with oesophageal cancer, and the clinical factors influencing it. Method: A total of 67 participants successfully completed the study, with 18 of them engaging in supervised, in-hospital aerobic training at moderate intensity for a minimum of 20 sessions. Cardiopulmonary exercise testing, hand grip strength, body composition assessed via bioelectrical impedance analysis, patient-generated subjective global assessment, albumin, and the Functional Oral Intake Scale (FOIS) were evaluated before chemoradiotherapy and 6-8 weeks after its completion. Result: Among the participants, cardiopulmonary fitness, hand grip strength, and phase angle of BC-BIA declined during chemoradiotherapy. Before and after chemoradiotherapy, V̇O2peak was 19.6 ± 4.4 and 17.4 ± 3.9 mL/min/kg respectively. The improvement in FOIS during chemoradiotherapy showed a positive correlation with changes in aerobic capacity. Additionally, exercise training was associated with attenuating the decline in aerobic capacity. Conclusion: Physical fitness deteriorated in patients with oesophageal cancer following chemoradiotherapy. Improvement in dysphagia helps maintain aerobic capacity. Additionally, exercise training has the potential to mitigate the decline. This discovery can serve as a reference for enhancing holistic care for patients with oesophageal cancer.